Gambaran kristal hemoglobin pada darah dan bercak darah yang terpapar beberapa sampo cuci mobil menggunakan tes Teichmann dan tes Takayama - Edward Sembiring; Enikarmila "; Tegar Indrayana (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
Bloodstain is very useful in crime scene disclosure through a series of forensic laboratory test. Attempted in removing evidence of bloodstain with cleaning agents such as car wash shampoo is a challenge in the investigation. Crystal hemoglobin test is a chemically confirmation that based on crystals formation of hemoglobin such as Teichmann and Takayama test. The purpose of this study is to observe crystal hemoglobin formation in blood and bloodstains exposed with car wash shampoo using Teichmann and Takayama test. This study is laboratory experimental descriptive. The study was conducted in biochemical laboratory of university of Riau medical faculty. Using 52 pieces slides with twice repetition (duplo). The slides were divided into blood and bloodstain slide group, which both group washed with A, B, and C car wash shampoo as much as one till three times continued with Teichmann and Takayama test. In the study was found that in all done slide either Teichmann or Takayama test the result is positive.Keywords: Bloodstain, hemoglobin crystal, car wash shampoo, Teichmann and Takayama1. PENDAHULUANPemeriksaan forensik tidak terbatas untuk luka yang ditemukan pada korban hidup atau mati saja tetapi juga dapat dilakukan pada benda atau barang bukti yang ditemukan di tempat kejadian. Salah satu barang bukti yang sering ditemukan adalah darah atau bercak darah. Keberadaan bercak darah ini sangat berguna dalam pengungkapan tindakan kekerasan atau kejahatan melalui serangkaian pemeriksaan laboratorium forensik.1 Salah satu contoh tindak kejahatan dengan barang bukti berupa darah atau bercak darah adalah pelanggaran ketertiban umum pada ketertiban lalu lintas yang berujung menjadi